Design and testing of a posture-adjusting precision metering device for high-speed maize planting - Dong, Jianxin; Gao, Xiaojun; Zheng, Zhouzhou; Zhao, Pengfei; Bi, Yubin; Huang, Yuxiang (Frontiers in Plant Science, 2025)
IntroductionThis study introduces a new technical method that involves adjusting the seed-filling posture and fluidizing the seed group to improve the capacity of mechanical seed-metering devices for high-speed maize planting. The design of a novel posture-adjusting seed-metering device is presented and its operating principle is described. In the seed-filling area, the seeds maintain the same postural characteristics and are detached from the seed group. This method creates favorable conditions for mechanical seed-metering devices to achieve effective seed-filling under high-speed planting conditions.MethodsFirstly, the key parameters of the core component were analyzed. Secondly, the influences of the seed posture adjusting efficiency and seed flow distribution characteristics on the seed-filling effect were clarified by the EDEM simulation. Finally, the high-speed metering performance was optimized and validated using bench testing.ResultsThe experiment demonstrated that the type A groove had the highest seed posture adjusting efficiency, a more uniform seed flow distribution, and a superior seed-filling effect as compared to the other groove types. The best metering performance was achieved with an opening angle of 21.6° and an opening width of 8.4 mm; this resulted in pass, repeat, and leak rates of 94.8%, 1.3%, and 3.9%, respectively. Within the speed range of 8–14 km/h, the posture-adjusting seed-metering device demonstrated a pass rate of over 94%, a repeat rate below 2.1%, and a leak rate below 3.9%.DiscussionThe designed device had a better high-speed planting capacity than a seed-metering device without a posture-adjusting mechanism, thus proving the effectiveness of the novel seed-filling method. These findings provide a reference for improving the high-speed planting capacity of mechanical seed-metering devices.